Alteración cromática por vapor de mercurio en chorreros de la Empresa Minera Hbd De Istmina-Chocó (2020)
The purpose of the present study is to demonstrate the prevalence of chromatic alterations in jets (miners) of the mining company HBD of Istmina Chocó, whose use entails a high exposure to mercury vapor while developing the melting process of the gold, gravel amalgam and liquid mercury without using any personal protection element.